Implementation Of Innovation And Literacy In Islamic Education Curriculum Development : Inovasi, Literasi, Pengembangan Kurikulum, MA Roudlatul ‘Ulum. - Mochamad Rofiq; Mohamad Ardin Suwandi (Jurnal Penelitian Multidisiplin, 2023)
As we know that the curriculum has an important role in the process of achieving educational goals, on the other hand, education must always develop and answer the challenges of changing times. Therefore, in developing the curriculum, innovation and literacy are needed so that education can achieve its goals optimally, especially in Islamic religious education. The purpose of this article is to conduct an in-depth analysis of the implementation of innovation and literacy in the development of the PAI curriculum at MA Raodlatul 'Ulum. This study uses a qualitative method with a literature study approach. Data collection uses a documentation study, while the data sources consist of books, articles, and other research results related to the problem being studied. The results of this study indicate that the implementation of innovation and literacy in curriculum development at MA Roudlatul 'Ulum uses an integrated curriculum, namely by integrating contemporary issues into the PAI curriculum, including through the subjects of Fiqh, Al-Qur'an-Hadith, Aqidah Akhlak, and History of Islam.